1974
DOI: 10.1039/f19747000072
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of halogens with oxide surfaces

Abstract: Charge transfer reactions at oxide surfaces are discussed for the halogens, chlorine, bromine and iodine as strong electron acceptors. Adsorption of chlorine and bromine on MgO prepared in vucuo is characterised by the appearance of a band at 430nm in the diffuse reflectance spectrum and an e x . signal with g-factors of 2.0099 and 2.0020. These features are destroyed on heating and oxygen is evolved. Chlorine and bromine react with the lattice oxygen ions to give halide ions corresponding to about 20 and 10 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

1974
1974
2015
2015

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 4 publications
0
5
1
Order By: Relevance
“…Those of MgO‐based systems whose surface has been modified with halides are much less investigated. There is some information in literature regarding the effect of modification of the MgO surface with halides on the activity of MgO as well as on the replacement of lattice oxygen of MgO by halides upon treatment of MgO with a halide‐containing compound or halogens …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Those of MgO‐based systems whose surface has been modified with halides are much less investigated. There is some information in literature regarding the effect of modification of the MgO surface with halides on the activity of MgO as well as on the replacement of lattice oxygen of MgO by halides upon treatment of MgO with a halide‐containing compound or halogens …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the formation of MgI 2 was not achieved by treatment of nano‐MgO with 1‐iodobutane, and the surface of the nanomaterial did not diminish as much as in the case of the other halides . A study performed by Kibblewhite and Tench conducted on MgO modified with Cl 2 , Br 2 , and I 2 showed that oxygen evolution resulting from exchange of the halogen with lattice oxygen is observed only for chlorine and bromine . This means that pronounced differences should be expected when comparing the surface properties of MgO modified with bromine and iodine.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among others this concerns the ident,ificat,ion of the ESR signal formed by bromine adsorpt,ion. Although in the light of the experiincnt'al data presented in this paper the simplest siiggest'ion would be to ascribe i t to the molecular ion Br;, there are some arguments, by analogy with the MgO-halogens system [13], that it. might be connected with oxide ions of the lattice destabilized to some extent.…”
Section: Resultsmentioning
confidence: 82%